Optimizing Writing Skills through the Integration of PjBL and Learning Media - Hakim, Lukman; Suhartono, Suhartono; Indarti, Titik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Writing is a crucial skill in Indonesian language learning, requiring the integration of cognitive, linguistic, and psychomotor aspects. However, the reality on the ground shows that students' mastery of writing skills is still suboptimal due to internal and external factors. This article discusses optimizing writing skills through the integration of the Project-Based Learning (PjBL) model and visual learning media. PjBL provides an authentic framework that motivates students through the completion of real projects and systematic stages, from determining fundamental questions to reflection. The integration of visual media serves as a visual stimulus that simplifies abstract information, stimulates critical thinking, and helps students organize ideas systematically into written text. The teacher's role transforms into a facilitator, mentor, and motivator who accompanies each phase of the project to ensure the achievement of learning objectives. Through this synergy, writing learning becomes more concrete, interactive, and meaningful for students.